Rural Entrepreneurship through Electricity (Hydro Nepal: Journal of Water, Energy and Environment, 2009)
Rural electrification in Nepal is supported mostly by bilateral donors and banks as a top down supply driven activity with emphasis on generation and transmission, but not focusing on supplying electricity to the maximum number of rural people. In the past, rural electrification was awarded as political favors, leading to inefficiency. Further, it could not further the efficient development of energy, which requires marketing innovation. The result of such rural power distribution created a condition where everybody was at fault and a loser. An innovative approach involving the rural communities has the potential of reversing this trend, and allowing communities themselves to manage local rural electrification systems. This approach has raised public interest in Community Development and Rural Electrification with the establishment of about 450 rural electricity communities in Nepal. In anticipation, these communities are willingly contributing 20% matching fund of total rural electrifi cation cost. Since 2003 to 2008, 189,770 households (about 45,000 households annually) have gotten access to electricity in rural areas through the promotion of community-based electricity development. Clearly, this is a signifi cant positive response from the rural population. Like community forestry before it, community rural electrifi cation is also a success story in Nepal. The new approach has paved the way to gender equality. It helped to generate more economic activities, to activate productive end use of electricity, developed rural entrepreneurship and released the poorest of poor population from the ‘bonds’ of the old social structure.Hydro Nepal: Journal of Water, Energy and Environment Issue No. 4, January, 2009 Page 36-39